FORMULASI TABLET EKSTRAK ANGKAK (RED YEAST RICE) DENGAN VARIASI CROSCARMELLOSE SODIUM SEBAGAI PENGHANCUR DAN LAKTOSA SEBAGAI PENGISI - Adestria Resti; Aris Perdana Kusuma; Achmad Fudholi (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
Angkak or better known as Red yeast rice is fermentation rice using a mold Monascus purpureus. Some studies of red yeast rice can lower cholesterol levels in the body because it contains monoakolin K or similliar with lovastatin compound. Generally in community consumption of red yeast rice only with pour in the boilling water so it can causing inconvenience for its customers. This study aims to make a formulation tablet of red yeast rice extract which varied with the levels of croscarmellose sodium 5% -1% (32mg, 26mg, 19,5mg, 13mg, 6,5mg) and lactose (75,75mg, 82.25 mg, 88,75mg , 95,25mg, 101,75mg) in order to get a best physical properties of the tablet including friability and disintegration time. Angkak extract was made by remaseration method using ethanol 75% and the manufacture of tablets using wet granulation method. Stastical test tablet extract angkak using One Way ANOVA with 95% confidence level. Optimum formula obtained by using the Simplex Lattice Design (SLD) using Design Expert version 8.0.7.1 program and statistically tested using one-sample t-test. The results from test showed the proportion of croscarmellose sodium 6.5mg and 101.75mg lactose produces tablets with the best of physical properties of red yeast rice extract.The result is indicate that the combination of croscarmellose sodium and lactose may affect response the physical properties of red yeast rice extract tablets.